A 571 million‐year‐old alkaline volcanic lake photosynthesizing microbial community, the Anti‐atlas, Morocco. Issue 2 (24th December 2020) - Chraiki, Ibtissam; Bouougri, El Hafid; Chi Fru, Ernest; Lazreq, Nezha; Youbi, Nasrrddine; Boumehdi, Ahmed; Aubineau, Jérémie; Fontaine, Claude; El Albani, Abderrazak
Abstract: The Ediacaran period coincides with the emergence of ancestral animal lineages and cyanobacteria capable of thriving in nutrient deficient oceans which together with photosynthetic eukaryotic dominance, culminated in the rapid oxygenation of the Ediacaran atmosphere. However, ecological evidence for the colonization of the Ediacaran terrestrial biosphere by photosynthetic communities and their contribution to the oxygenation of the biosphere at this time is very sparse. Here, we expand the repertoire of Ediacaran habitable environments to a specific microbial community that thrived in an extreme alkaline volcanic lake 571 Myr ago in the Anti‐atlas of Morocco. The microbial fabrics preserve evidence of primary growth structures, comprised of two main microbialitic units, with the lower section consisting of irregular and patchy thrombolytic mesoclots associated with composite microbialitic domes. Calcirudite interbeds, dominated by wave‐rippled sandy calcarenites and stromatoclasts, fill the interdome troughs and seal the dome tops. A meter‐thick epiclastic stromatolite bed grading upwards from a dominantly flat to wavy laminated base, transitions into low convex laminae consisting of decimeter to meter‐thick dome‐shaped stromatolitic columns, overlies the thrombolitic and composite microbialitic facies. Microbialitic beds constructed during periods of limited clastic input, and underlain by coarse‐grained microbialite‐derived clasts and by the wave‐rippled calcarenites, suggest high‐energy events associated with lake expansion. High‐resolution microscopy revealed spherulitic aggregates and structures reminiscent of coccoidal microbial cell casts and mineralized extra‐polymeric substances (EPS). The primary fabrics and multistage diagenetic features, represented by active carbonate production, photosynthesizing microbial communities, photosynthetic gas bubbles, gas escape structures, and tufted mats, suggest specialized oxygenic photosynthesizers thriving in alkaline volcanic lakes, contributed toward oxygen variability in the Ediacaran terrestrial biosphere.